Entering the Political Climate, Whether Policy Makers Are Becoming More Responsive to Public Demand - Septian, Hendy; Bantara, Prihanto Haidi; Iswanto, Dani (Dinasti International Journal of Digital Business Management, 2023)
The results underscore the importance and usefulness of our concept and empirical measures for public demand, as well as of our disaggregated analysis of climate policy outputs in this area, Normative theories o democracy agree that public demand should be the main guide in policymaking. But positive theories and related empirical research disagree about the extent to which this holds true in reality. We Address this debate with an empirical focus on climate change policy. Specifically, we are interested in whether observable variation in public demand for climate change mitigation can help explain variation in adopted national climate policies. Using our own data approximate public demand, we estimate the responsiveness of policymakers are responsive and react in predicted ways to variation in our opinion component of measured public demand, rather than to mere salience of the climate issue. The effect of issue salience is strongest in combination with our opinion measure as this creates a scope for action